Breast Cancer Prediction Using Clustering Techniques - Karmakar, Priyabrata; Dalui, Debolina; Singh, Dharmpal; Nath, Ira (International Journal of Computer Sciences and Engineering, 2025)
Data mining is the process of extracting hidden interesting patterns from massive database. It is used to extract the hidden information/knowledge from the real-life database. It also has use in the medical field. Thus want to apply concept of data mining into breast cancer prediction. According to many surveys, it has been observed that all over the world most of the women are dying in breast cancer in recent days. So, we have made an effort to design the knowledge base using clustering technique on the data. We have applied the hierarchical clustering and found the error is 2.13%. The K means and fuzzy C means will be applied in the future to minimize the error further.